Age-Related Patterns in Cancer Pain and Its Psychosocial Impact: Investigating the Role of Variability in Physical and Mental Health Quality of Life. Issue 4 (3rd March 2017) - Gauthier, Lynn R; Dworkin, Robert H; Warr, David; Pillai Riddell, Rebecca; Macpherson, Alison K; Rodin, Gary; Zimmermann, Camilla; Lawrence Librach, S; Moore, Malcolm; Shepherd, Frances A; Gagliese, Lucia
Abstract: Objective: Age-related patterns in cancer pain remain equivocal. Most studies ignore heterogeneity across multiple domains of well-being, and the potential role of physical (PH) and mental health (MH) quality of life (QOL) in these age-related patterns is unknown. We investigated the relationships between age and cancer pain intensity, qualities, and interference, and physical and psychosocial adaptation and the interaction between age and PH and MH QOL on pain and adaptation to cancer pain. Design: In this cross-sectional study, 244 patients with advanced cancer and pain completed measures of pain, QOL, physical function, and psychosocial well-being. Pearson's correlations and ANOVAs assessed relationships between age and demographic and clinical factors, pain, and physical and psychosocial measures. Regression models tested the role of age and its interaction with PH and MH QOL on pain and physical and psychosocial adaptation. Results: Older age was associated with a lower likelihood of receiving an opioid prescription, greater likelihood of having comorbidities, and worse functional status. When we did not account for these factors, age was not associated with pain and most adaptation indices. When we did account for these factors and PH QOL, older age was associated with lower non-neuropathic and neuropathic pain and several indices of psychosocial adaptation. Most interestingly, older age was associated with lower non-neuropathic pain among those with high, but not low, MH QOL. Conclusions: This study addresses knowledge gaps about factors underlying age-related patterns in cancer pain. Impaired MH QOL may be a proxy for age-related patterns in cancer pain. Summary: This study investigated age-related patterns in the experience of cancer pain and the role of quality of life in resilience and vulnerability to pain and adaptation to pain. Older age is associated with lower non-neuropathic pain among those with high, but not low, mental health quality of life, suggesting that impaired mental health quality of life is an important indicator of vulnerability to multidimensional pain outcomes.